PERBANDINGAN LOGISTIC PERFORMANCE INDEX (LPI) DAN PURCHASING MANAGER’S INDEX (M-PMI) DALAM MENGEVALUASI KINERJA LOGISTIK INDONESIA - SUBEKTI SUBEKTI; DEVI JAYAWATI (Politeknik APP Jakarta, 2017)
The effectiveness of Logistics system is the main pillar for national industry and trade development and also for foreign investment attractiveness. Logistics performance at the macro or national level is evaluated using LPI (Logistics Performance Index) that issued by the World Bank. Beside that, the other one of economic indicators is M-PMI (Manufacturing Purchasing Managers Index) that evaluates the economic development of a country whether there is an increasing of the level of production, delivery of goods by the supplier, and inventory levels in the processing industry. This study fills a gap in assessing the relationship between LPI dan M-PMI. This study discusses the three things, firstly the condition of LPI Indonesia and the potential for improvement, secondly conditions M-PMI Indonesia 2013 - 2015, and thirdly, the relationship between M-PMI and LPI which analyze the impact of the changes of LPI values to the value of M-PMI. We use comparative analysis qualitatively. From the data analysis of LPI value in 2014 it shows that compared to the other ASEAN countries, Indonesia still needs a lot of improvement in customs clearance and delivery components. From the M-PMI curve it shows that when Indonesia’s LPI is 2,94 in 2012 the value of Indonesia’s M-PMI fluctuate with variation of 2.29. Meanwhile, when Indonesia’s LPI is 3.08 in 2014, the value of the Indonesia’s M-PMI more stable with a variation of 1, 69. We can conclude that the condition M-PMI will be more stable when the LPI is higher, but the movement of M-PMI was not significantly affected by LPI itself but rather on economic conditions, especially the interest rate, purchasing power, and the productivity of the manufacturing industry.